2009
DOI: 10.1183/09031936.00186908
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular dysfunction in end-stage cystic fibrosis: role of NF-κB and endothelin-1

Abstract: Pulmonary hypertension is rare in chronic respiratory diseases but has a strong impact on the prognosis and is partly underlined by factors other than hypoxaemia. The aim of the present study was to assess the potential role of endothelin-1 (ET-1) and nuclear factor (NF)-kB vasoconstrictive pathways in pulmonary hypertension.The effects of ET-1 receptors blockers (BQ 123 and 788) and of genistein were assessed on response to acetylcholine of pulmonary vascular rings from cystic fibrosis (CF) lung transplant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
(56 reference statements)
1
24
0
Order By: Relevance
“…It is likely that use of a threshold value of S pO 2 Ͻ 90% identifies a group with lower absolute oxyhemoglobin saturation during exercise and may reflect a greater impairment of the pulmonary vasculature, thought to occur frequently in end-stage CF. 20 This highlights the importance of using standardized definitions for desaturation, in order to compare data across trials.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that use of a threshold value of S pO 2 Ͻ 90% identifies a group with lower absolute oxyhemoglobin saturation during exercise and may reflect a greater impairment of the pulmonary vasculature, thought to occur frequently in end-stage CF. 20 This highlights the importance of using standardized definitions for desaturation, in order to compare data across trials.…”
Section: Discussionmentioning
confidence: 99%
“…accordingly to previous experiments done in an historical group of non smokers. We previously demonstrated that the decrease in vascular reactivity was not due to endothelial damage during manipulations [7].…”
Section: Arterial Experimentsmentioning
confidence: 92%
“…Arterial rings were evaluated immediately after dissection, whereas bronchial rings were placed in oxygenated Krebs's solution and stored overnight at 4°C, as previously described [5,7,8].…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…It has also been shown to be induced by oxidants with such induction also lowered by antioxidants [202][203][204]. e activity of ET-1 has been shown to be increased by both NF-B action and also the action of another in�ammatory cytokine activated pathway [205][206][207]. us, the in�ammatory part of the NO/ONOO − cycle has a powerful role in increasing ET-1 activity.…”
Section: Principlementioning
confidence: 99%
“…It increases oxidative stress [211][212][213][214][215][216][217], superoxide [211,[213][214][215][216], the ONOO − marker 3-nitrotyrosine [211,212], NF-B activity [211,217], and NO [211,213,218], lowers levels of BH4 [213-215, 217, 219], stimulates iNOS induction [211,217], increases TRP receptor function [220,221], increases levels of intracellular calcium [222][223][224], increases NMDA activity [225,226], produces mitochondrial dysfunction [227,228], and increases in�ammatory cytokine levels [206,207,217]. All of these provide evidence for elevation of each of the NO/ONOO − cycle elements.…”
Section: Principlementioning
confidence: 99%